2016
DOI: 10.5812/numonthly.35356
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Ultrasound-Guided Transversus Abdominis Plane Block After Nephrectomy; Postoperative Pain and Use of Opioids

Abstract: BackgroundPain has a wide spectrum of effects on the body and inadequately controlled postoperative pain may have harmful physiologic and psychological consequences and increase morbidity. In addition, opioid anesthetic agents in high doses can blunt endocrine and metabolic responses following surgery and are associated with side effects including dizziness, nausea, vomiting, constipation, and respiratory depression.ObjectivesThe current study aimed to investigate if unilateral ultrasound-guided transverse abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
0
16
0
1
Order By: Relevance
“…On the other side, Azawietal (2016) found that local anesthetic wound in ltration was superior to the TAP block concerning postoperative analgesia after laparoscopic nephrectomy [20]. J. Kessler, also found that TAP block did not improve postoperative quality of recovery (QoR-40) for patients undergoing total laparoscopic hysterectomy [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, Azawietal (2016) found that local anesthetic wound in ltration was superior to the TAP block concerning postoperative analgesia after laparoscopic nephrectomy [20]. J. Kessler, also found that TAP block did not improve postoperative quality of recovery (QoR-40) for patients undergoing total laparoscopic hysterectomy [21].…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of TAP block has been compared with placebo or local anaesthetic wound infiltration in various surgeries such as cesarean deliveries, open gynecologic procedures, nephrectomy, and inguinal hernia repair. [ 12 13 14 15 16 ] Analgesia achieved through local anaesthetic infiltration of the subcutaneous or subfascial planes of the wound has different mechanisms of action including simple local anaesthesia, anti-inflammatory effect, and systemic absorption of the local anaesthetic. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are consistent with the findings of other studies. 18,[23][24][25][26][27] The haemodynamic parameters remained stable perioperatively with both drugs used in TAP block. The results are in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%